Acute vulval edema leading to urinary retention in a lady with pre-eclampsia: case report - Mane, Jitendra D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Acute urinary retention is condition which requires immediate attention as it is associated with severe pain and which is relieved by simple procedure of catheterization. This complication is uncommon in women compare to males. It is much rarer during pregnancy. Presenting a case of acute retention of urine in a primigravida woman with vulval edema having severe pre-eclampsia in third trimester. She was initially managed with indwelling Foleys catheter followed by delivery which relieved her symptoms.